2004
DOI: 10.1074/jbc.m402245200
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Mitochondrial Proteome in Response to the Stress of Ethanol-dependent Hepatotoxicity

Abstract: Mitochondria are particularly susceptible to increased formation of reactive oxygen and nitrogen species in the cell that can occur in response to pathological and xenobiotic stimuli. Proteomics can give insights into both mechanism of pathology and adaptation to stress. Herein we report the use of proteomics to evaluate alterations in the levels of mitochondrial proteins following chronic ethanol exposure in an animal model. Forty-three proteins showed differential expression, 13 increased and 30 decreased, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
163
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(182 citation statements)
references
References 66 publications
18
163
1
Order By: Relevance
“…19 Furthermore, increased degradation of oxidatively modified proteins may contribute to the reduced levels of several hepatic mitochondrial proteins such as ATP synthase and 3-ketoacyl-CoA thiolase in alcohol-exposed rats, as previously reported. 27,28 Our 2-D PAGE and MS analyses also revealed that many protein spots, though identified as being the same protein, exhibited different pI values that possessed the same or similar apparent masses. For example, several proteins with apparently different pI values were each identified as ALDH2 (spots 3,6-8,11,13,53,54), ATP synthase (spots 6-13), 3-ketoacyl-CoA thiolase (spots 15-24), electron-transfer flavoprotein ␤ subunit (spots 26-30 and 32-34), and MDH (spots 55-67).…”
Section: Resultsmentioning
confidence: 99%
“…19 Furthermore, increased degradation of oxidatively modified proteins may contribute to the reduced levels of several hepatic mitochondrial proteins such as ATP synthase and 3-ketoacyl-CoA thiolase in alcohol-exposed rats, as previously reported. 27,28 Our 2-D PAGE and MS analyses also revealed that many protein spots, though identified as being the same protein, exhibited different pI values that possessed the same or similar apparent masses. For example, several proteins with apparently different pI values were each identified as ALDH2 (spots 3,6-8,11,13,53,54), ATP synthase (spots 6-13), 3-ketoacyl-CoA thiolase (spots 15-24), electron-transfer flavoprotein ␤ subunit (spots 26-30 and 32-34), and MDH (spots 55-67).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, this decrease in ADP-stimulated respiration is linked to decreased electron transport in all segments of the respiratory chain as chronic alcohol consumption decreases the activities of all the respiratory complexes, except complex II [41,42]. Several laboratories have presented strong evidence that inhibition of mitochondrial protein synthesis [43] linked to mtDNA damage [44][45][46] and ribosomal defects [47,48] contribute, in part, to decreased functioning of the oxidative phosphorylation system following chronic alcohol consumption. These alterations translate into profound modifications to the mitochondrial proteome that encompass not only losses in the 13 mitochondrial encoded polypeptides, but also decreases in numerous nuclear encoded proteins that make up the oxidative phosphorylation complexes [46].…”
Section: Mitochondria Dysfunction In Fatty Liver Diseases -Bioenergetmentioning
confidence: 99%
“…Several laboratories have presented strong evidence that inhibition of mitochondrial protein synthesis [43] linked to mtDNA damage [44][45][46] and ribosomal defects [47,48] contribute, in part, to decreased functioning of the oxidative phosphorylation system following chronic alcohol consumption. These alterations translate into profound modifications to the mitochondrial proteome that encompass not only losses in the 13 mitochondrial encoded polypeptides, but also decreases in numerous nuclear encoded proteins that make up the oxidative phosphorylation complexes [46]. Proteomic analyses have also shown alcohol-dependent changes in mitochondrial matrix enzymes both at the level of abundance and post-translational modifications [46,49,50].…”
Section: Mitochondria Dysfunction In Fatty Liver Diseases -Bioenergetmentioning
confidence: 99%
See 2 more Smart Citations